MicroRNAs as Biomarkers and Therapeutic Targets for Medulloblastomas - O. A. Beylerli; I. F. Gareev; A. B. Alyshov; V. V. Kudriashov (Креативная хирургия и онкология, 2020)
Medulloblastomas (MBs) are the most common malignant neoplasms of the central nervous system in children. MB is a persistent disease associated with a high level of morbidity and mortality, thus requiring aggressive therapeutical approaches. Clinical and histological features of tumours are used for their classification and prognosis. Despite significant progress in the study of MB, its molecular basis remains to be fully understood.  MicroRNAs (miRNAs) are short noncoding RNAs (ncRNAs) that function as key regulators of various biological processes, including the development, differentiation, metabolism, proliferation and apoptosis of cells. MiRNAs regulate genes at the posttranscriptional level. Aberrant expression of miRNAs correlates with various cancers. This altered expression may result from mutation, methylation, deletion and amplification of miRNA coding regions. In this review, we discuss the role of miRNAs in MB and their potential use in the diagnosis, prognosis and treatment of this malignant tumour. As a fastgrowing field in biomedical sciences, miRNAs studies will revolutionize the treatment of MB.